2019
DOI: 10.1111/cge.13607
|View full text |Cite
|
Sign up to set email alerts
|

Development of a measure of genome sequencing knowledge for young people: The kids‐KOGS

Abstract: Genome sequencing (GS) is increasingly being used to diagnose rare diseases in paediatric patients; however, no measures exist to evaluate their knowledge of this technology. We aimed to develop a robust measure of knowledge of GS (the kids‐KOGS') suitable for use in the paediatric setting as well as for general public education. The target age was 11 to 15 year olds. An iterative process involving six sequential stages was conducted to develop a set of draft true/false items. These were then administered to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…To chart and extract data from the articles selected for the scoping review, an extraction criterion was developed by 2 reviewers (AG and MT) to extract information from each publication about the study country, city, urban or not urban geography, population, sample size, age of participants, pediatric disease types, duration, demographic information, design, methodology, journal of publication, and results of the study (Multimedia Appendix 2 [3,12,16,[33][34][35][36][37][38][39][40][41][42][43]).…”
Section: Data Items and Data Charting Processmentioning
confidence: 99%
See 2 more Smart Citations
“…To chart and extract data from the articles selected for the scoping review, an extraction criterion was developed by 2 reviewers (AG and MT) to extract information from each publication about the study country, city, urban or not urban geography, population, sample size, age of participants, pediatric disease types, duration, demographic information, design, methodology, journal of publication, and results of the study (Multimedia Appendix 2 [3,12,16,[33][34][35][36][37][38][39][40][41][42][43]).…”
Section: Data Items and Data Charting Processmentioning
confidence: 99%
“…Of the 14 studies, 5 (36%) studies included populations where children were clinically diagnosed with various genetic conditions [16,[33][34][35][36]; 4 (29%) studies had populations that were not diagnosed with an illness [12,[37][38][39]; 1 (7%) study included children who were suspected to have a genetic condition but not diagnosed [40]; 1 (7%) study included children who were hospitalized for various reasons [3]; and the remaining 3 (21%) studies reported pediatric populations with illnesses such as cancer [41], congenital heart defects [42], and congenital lower limb deficiencies [43]. Most (11/14, 79%) of the studies selected for the review were from the United States [3,12,[33][34][35][36][38][39][40][41][42], 14% (2/14) from Canada [16,43] and 7% (1/14) from the United Kingdom [37]. Table 1 presents the overview of the included studies.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed a quantitative survey which was implemented at two time-points; time 1 (T1) before watching the animation and time 2 (T2) after watching the animation (Supplementary Material 5). The survey was adapted from one developed by Sanderson et al [21] to evaluate the animation "Whole Genome Sequencing and You" [3] and included a new knowledge of genome sequencing measure for young people (the kids-KOGS) [22].…”
Section: Survey Developmentmentioning
confidence: 99%
“…Responders were also asked "How would you describe your understanding of genetics" (None, Some, Good). Objective knowledge was assessed using the new 10-item kids-KOGS [22] which includes a series of statements about GS with responders asked to indicate whether the statement is true, false or don't know.…”
Section: Survey Developmentmentioning
confidence: 99%